2015
DOI: 10.1002/gps.4292
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depressive symptoms and oral health outcomes in a community sample of older adults

Abstract: Objective Adverse outcomes associated with chronic depressive symptoms are of clinical importance. The objective was to identify subgroups of older adults based on their trajectories of depressive symptoms over a ten-year period, and determine if these subgroups predicted oral health outcomes. Methods Secondary analysis of data from the Health and Retirement Survey. The sample was 944 adults age 65+ who participated in the oral health module in 2008. Depressive symptoms were measured with a modified version … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 25 publications
5
46
3
Order By: Relevance
“…The authors found no differences in blood pressure, blood glucose or cholesterol between the different depression trajectory classes. Hybels et al (2015) found that older adults with depression trajectories characterized by higher symptom burdens were more likely to experience oral health problems. Several studies (Andreescu et al, 2008; Liang et al, 2011; Kuchibhatla et al, 2012) found that trajectories with higher depressive symptom burden were associated with higher mortality among older adults.…”
Section: Resultsmentioning
confidence: 95%
“…The authors found no differences in blood pressure, blood glucose or cholesterol between the different depression trajectory classes. Hybels et al (2015) found that older adults with depression trajectories characterized by higher symptom burdens were more likely to experience oral health problems. Several studies (Andreescu et al, 2008; Liang et al, 2011; Kuchibhatla et al, 2012) found that trajectories with higher depressive symptom burden were associated with higher mortality among older adults.…”
Section: Resultsmentioning
confidence: 95%
“…For instance, memory and executive function losses can compromise their ability to perform oral hygiene in a regular and appropriate fashion . Depression may influence oral health through biological pathways such as disruption of the immune system and hyposalivation linked to antidepressants; or nonbiological pathways, such as reduced self‐care and reduced usage of dental services due to depressive symptoms . Cognitive enhancing drugs like cholinesterase inhibitors and memantine, used to treat Alzheimer's disease, have not been shown to have significant oral side effects.…”
Section: Oral Health Status Among Patients With Alzheimer's Diseasementioning
confidence: 99%
“…46 ROHD risk factors are related to three main groups, that is, general health conditions, social support, and oral health conditions. 46 Among the ROHD risk factors related to general health, neurodegenerative conditions and dementia are considered as significant risk factors and treatment plan modifiers, 7,11 as well as conditions that often accompany dementia, like depression 47 and polypharmacy. 48,49 Older adults with cognitive impairment have many functional losses that can impair their ability to keep their oral hygiene routines.…”
Section: Risk Factors For Rapid Oral Health Deterioration (Rohd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Common systemic health problems among the elderly that cause a decline in general function include, but are not limited to, neuro-degenerative conditions and dementia, [13][14][15] diabetes, [16][17][18] depression, 15,19 polypharmacy, 18,20,21 arthritis, 17 and stroke. 17,22 These systemic health problems can impact oral health in many ways.…”
mentioning
confidence: 99%